Effects of forward head posture on the centre of pressure sway duringdual-task balancing with smartphone engagement - Tapanya, Weerasak; Sangkarit, Noppharath (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Forward head posture (FHP) may affect postural stability and balance. This study examines how smartphonetexting while balancing, as a dual task, influences the body’s centre of pressure (CoP) during single-leg standing in individualswith FHP compared to those with normal posture.Methods. The study utilized a randomized repeated measures design to assess single-leg standing balance and CoP acrosssix conditions. Fifty participants, divided into two groups (25 with FHP and 25 with normal posture), underwent testingsequences involving non-smartphone usage (NU; single task), one-handed smartphone usage (1H; dual task), and two-handedsmartphone usage (2H; dual task) on both soft and hard surfaces.Results. The study found that individuals with FHP showed increased CoP sway compared to those with normal postureacross all conditions. Both 1H and 2H increased sway compared to non-usage for both groups, with a notable difference inFHP individuals on soft surfaces, where 2H led to greater sway.Conclusions. Individuals with FHP are at a higher risk of balance issues during both NU and smartphone use, particularlyduring 2H. These results highlight the importance of addressing the impact of FHP on balance control and implementinginterventions to reduce associated risks.
Keywords: centre of pressure; postural stability; forward head posture; balance control; smartphone texting